In search of experiential knowledge. Issue 1 (2nd January 2017) - Blume, Stuart
Abstract : In recent years, the concept of "experiential knowledge" has increasingly been used to characterize the distinctive contribution patients make to decision-making in the health field. Even though it seems well-nigh impossible to characterize it precisely, there is no doubting its significance for decision-making contexts ranging from the individual to the political. Since individual experiences of any condition or treatment differ widely, whose experiences come to constitute "knowledge"? In this paper, I argue that, rhetoric notwithstanding, numerous constraints "filter" the experiences which come to function as "experiential knowledge". Looking to the future of health care, likely to be marked by growing inequalities, I suggest that a reflection on the notion of experiential knowledge leads to two challenges for social scientists.